Synthesis and Characterization of a 2D Cobalt(II) Coordination Polymer Containing the Adiponitrile Ligand1. Issue 12 (7th August 2013) - Chainok, Kittipong; Saphu, Watcharin; Khemthong, Phailyn; Harding, David J.
Abstract The cobalt(II) coordination polymer [Co(ADN)3][FeCl4]2 (1), which contains a flexible dinitrile bridging ligand was synthesized at room temperature from the 1:2:3 reaction of CoCl2, FeCl3, and adiponitrile (ADN) in CH3NO2. The compound was characterized by spectroscopic methods and single‐crystal X‐ray diffraction. The structure of 1 consists of a 2D sheet structure of [Co(ADN)3]2+ cations, the charge balance is maintained by [FeCl4]– anions. Each central CoII atom is coordinated by six nitrogen atoms from four gauche‐ and two anti ligands, adopting a distorted octahedral arrangement. The [FeCl4]– anions sit in channels created by the [Co(ADN)3]2+ cations, and link the 2D sheets into a 3D structure by weak C–H···Cl hydrogen bonds. The framework structure of 1 is thermally stable up to 285 °C.